MicroRNAs in Methamphetamine-Induced Neurotoxicity and Addiction - Deng, Bi; Zhang, Zhirui; Zhou, Huixuan; Zhang, Xinran; Niu, Shuliang; Yan, Xisheng; Yan, Jie (Frontiers in Pharmacology, 2022)
Methamphetamine is a widely abused psychostimulant owing to its strong addictive properties. Prolonged abuse of the drug can cause irreversible damage to the central nervous system. To date, no efficient pharmacological interventions are available, primarily due to the unknown mechanisms underlying the action of methamphetamine in the brain. Recently, microRNAs (miRNAs) have been identified to play critical roles in different cellular processes. It was revealed that the expression levels of some miRNAs are altered after methamphetamine administration, which may act on the target genes to regulate methamphetamine-induced toxicity or addiction. The potential regulatory effect of miRNAs provides new clinical insights for the intervention of methamphetamine abuse. We hope that further exploration of the accurate role of miRNAs in methamphetamine-related reward effects and neurological disorders, as well as overcoming its application insufficiency will contribute to successfully reducing related harm induced by the drug.